2007
DOI: 10.1007/s00705-007-1073-3
|View full text |Cite
|
Sign up to set email alerts
|

Point mutations in helper component protease of clover yellow vein virus are associated with the attenuation of RNA-silencing suppression activity and symptom expression in broad bean

Abstract: Helper component protease (HC-Pro) is a potyvirus-encoded multifunctional protein and a major determinant of symptom expression in a susceptible plant. Here, we show the involvement of clover yellow vein virus (ClYVV) HC-Pro in necrotic symptom expression in broad bean (Vicia faba cv. Wase). In this host, lethal necrosis was induced by ClYVV no. 30, from which a spontaneous, mosaic-inducing mutant (MM) was obtained. Mapping with chimeric viruses between ClYVV no. 30 and MM attributed the symptom attenuation to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
50
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 37 publications
1
50
0
Order By: Relevance
“…This condition is amply fulfilled by viral silencing suppressors. For example, 1 focusing only on potyviruses, it has been shown that two amino acid replacements in the HC-Pro suppressor of Clover yellow vein virus are sufficient to attenuate the symptoms and reduce virus accumulation (Yambao et al 2008), whereas a single mutation in Plum pox virus HCPro had a similar effect (González-Jara et al 2005). As a final example, mutations in the conserved motifs of Zucchini yellow mosaic virus HC-Pro also produced attenuated viruses on the natural host squash and also abolished the ability to elicit hypersensitive responses in other local lesion hosts (Lin et al 2007).…”
mentioning
confidence: 99%
“…This condition is amply fulfilled by viral silencing suppressors. For example, 1 focusing only on potyviruses, it has been shown that two amino acid replacements in the HC-Pro suppressor of Clover yellow vein virus are sufficient to attenuate the symptoms and reduce virus accumulation (Yambao et al 2008), whereas a single mutation in Plum pox virus HCPro had a similar effect (González-Jara et al 2005). As a final example, mutations in the conserved motifs of Zucchini yellow mosaic virus HC-Pro also produced attenuated viruses on the natural host squash and also abolished the ability to elicit hypersensitive responses in other local lesion hosts (Lin et al 2007).…”
mentioning
confidence: 99%
“…1G). In previous studies, we revealed that the HC-Pro gene is indirectly involved in the induction of lethal systemic cell death in PI 118501 (20,22,32). We found that a Cl-No.30 mutant with a D-to-Y substitution at amino acid position 193 of HC-Pro (Cl-D193Y) loses the ability to induce cell death in PI 118501 (20).…”
Section: Discussionmentioning
confidence: 93%
“…Extremely high virulence of ClYVV has been observed for many pea cultivars: ClYVV systemically induces cell death, resulting in plant death within 2 weeks when used to infect young plants (20)(21)(22) (Table 1). We previously reported that cell death induced by Cl-No.30 in pea cultivar PI 118501 is a form of an HR-like response accompanied by the activation of the salicylic acid (SA) pathway, which is one of the hallmarks of an HR (20).…”
mentioning
confidence: 99%
“…1c, there are also reports of attenuated potyviruses (Chiang et al 2007;Lin et al 2007b;Yambao et al 2008). When an attenuated strain (HA5-1) of PRSV was compared with its parent strain HA using an infectious cDNA clone, two amino acid substitutions among three in the C-terminal region of P1 at aa positions 309 and 481, and two of four in HC-Pro at aa positions 753 and 944 of HA5-1 appear to be critical in symptom attenuation in papaya (Chiang et al 2007).…”
Section: Potyvirusmentioning
confidence: 99%
“…When an attenuated strain (HA5-1) of PRSV was compared with its parent strain HA using an infectious cDNA clone, two amino acid substitutions among three in the C-terminal region of P1 at aa positions 309 and 481, and two of four in HC-Pro at aa positions 753 and 944 of HA5-1 appear to be critical in symptom attenuation in papaya (Chiang et al 2007). In a comparison of attenuated and severe strains of Clover yellow vein virus (ClYVV), two amino acid substitutions in HC-Pro were found to be responsible for symptom attenuation (Yambao et al 2008). Both mutations caused weaker RNA silencing suppression than the wild type did, suggesting a correlation between viral virulence and silencing suppression activity.…”
Section: Potyvirusmentioning
confidence: 99%